2021
DOI: 10.1177/21582440211006054
|View full text |Cite
|
Sign up to set email alerts
|

How Does Corporate Environmental Strategy Contribute to Voluntary Environmental Behavior? Influence of Psychological Green Climate, Firms’ Size, and Employees’ Age

Abstract: Considering the gravity of issues, the present study investigates the influence of corporate environmental strategy (CES) on the voluntary environmental behavior (VEB) of employees along with the potential moderating variables. The research questions and hypotheses are built based on the essence of an integrated theory of corporate environmental behavior and social identity theory. Data were collected from numerous organizations and analyzed following the deductive reasoning approach. Partial least square–base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Researchers have begun to acknowledge that eco-friendly behaviors and practices are highly beneficial to both organizations and the environment (Biswas et al, 2021;Frese et al, 1997;Uddin et al, 2020).…”
Section: Voluntary Environmental Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers have begun to acknowledge that eco-friendly behaviors and practices are highly beneficial to both organizations and the environment (Biswas et al, 2021;Frese et al, 1997;Uddin et al, 2020).…”
Section: Voluntary Environmental Behaviormentioning
confidence: 99%
“…An organization implementing green managerial practices wants to add value far beyond economic requirements, by taking environmental benefits into account and also informing employees that the organization cares about environmental issues in its production and manufacturing processes (Tang et al, 2018). It is evident that people who feel more positive about the environment, and who have a more mature awareness of the need to protect it, are more likely to display positive VEB that goes beyond their regular job duties (Biswas et al, 2021). To this end, the main purpose of the organization's activities is to raise employees' awareness of "green" issues (Hameed et al, 2020).…”
Section: Psychological Green Climate and Voluntary Environmental Beha...mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated the influences of gender on employees' pro-environmental behaviors (e.g., women tend to behave more environmentally; Vicente-Molina et al, 2018); therefore, we controlled for gender (1 = male; 2 = female) in the present study. In addition, considering that elderly individuals may be more concerned about the betterment of the environment through displaying green activities (Biswas et al, 2021), we controlled employees' age (in years). Since a recent review shows that when employees have a higher level of education, their environmental behaviors would arise (Lu et al, 2017), we control participants' educational level (1 = High school/ technical school and below; 2 = Bachelor's degree; and 3 = Master's degree and above).…”
Section: Control Variablesmentioning
confidence: 99%